Total testosterone and asymmetric dimethylarginine: Association of demographic, clinical and lifestyle factors with the severity of erectile dysfunction / Ray Mond Mark Joseph - Ray Mond Mark, Joseph (2018)
Erectile dysfunction (ED) is a highly prevalent disorder reported in men worldwide. ED is commonly associated with aging as well as with several other factors including demographic, clinical and lifestyle factors. However, scarce studies were reported on the combined association of demographic, clinical and lifestyle factors with worsening of severity of ED. Besides, few biomarkers too were proved to be significantly associated with ED and it is believed that demographic, clinical and lifestyle factors may have been one of the reasons which influence changes of biomarker levels in ED patients. However, these factors have not been studied extensively. Hence, this study was conducted to investigate the association of demographic, clinical and lifestyle factors with severity of ED and biomarker levels, namely total testosterone (TT) and asymmetric dimethylarginine (ADMA), and build the predictor models for severity of ED and related biomarkers. This cross sectional study involved 276 patients. Data were recruited from patients attending ED and medical clinics in University Malaya Medical Centre, a tertiary teaching hospital in Malaysia. The demographic, clinical, lifestyle factors and severity of ED were assessed using questionnaire included with the International Index of Erectile Function (IIEF-5). Meanwhile, TT and ADMA levels were determined using the enzyme-linked immunosorbant assay (ELISA). Binary logistic regression test was used to demonstrate the predictors of severity of ED, TT and ADMA levels. Significant predictors for worsening of severity of ED are [presented as adjusted odds ratio (95% confidence interval), p value] self-employed [10.55 (0.43 – 257.06), p=0.004], pensioner [8.07 (0.19 – 352.45), p=0.026], non-government employee [1.16 (0.05 – 26.26), p=0.04] and TT [0.41 (0.25 – 0.69), p=0.001]. Nevertheless, demographic and lifestyle factors were found to be the significant predictors for both TT and ADMA levels. Pensioner [0.08 (0.01 – 0.87), p=0.038] and unemployed [0.04 iv (0.01 –0.42), p=0.007], are the predictors which may predict the changes of TT levels. On the other hand, academic qualification (secondary) [4.51 (0.48 – 42.83), p=0.014] and intensity of physical activities (< 1 hour/day) [2.61 (0.65 – 10.48), p=0.008] were the predictors which more likely influence the changes of ADMA levels in ED patients. In conclusion, demographic and lifestyle factors predominate clinical factors in influencing TT and ADMA levels. Demographic and clinical factors predict the worsening of severity of ED in Malaysian ED population. Identification of these predictors influencing severity of ED, TT and ADMA may help to upgrade our knowledge on risk factors of ED. Thus, these predictive models may serve as new indicators in providing primarily guidance to physicians and ensuring ED can be managed and treated more effectively.